Validation of an educational technology on healthy eating among university students (Revista Contexto & Saúde, 2025)
Objective: To validate an educational technology on healthy eating among university students. Method: This is a quantitative study, developed at private universities in São Luís-MA from May to October 2022, with three study groups: target audience (n=24), health expert judges (n=22) and communication expert judges (n=13). Data collection from each group was carried out through digital questionnaires produced in Google Forms and was evaluated using a Likert scale. Aspects of content, writing, appearance, motivation, language, graphic illustration, cultural and content adequacy, objective and relevance were evaluated. To validate the e-book, the Content Validity Index (CVI) was used. Results: The e-book presented a total CVI of 0.97, a validation index considered adequate. The overall CVI for the target audience was 0.97; for the health expert judges, the content was validated with a CVI of 0.95; and for the communication judges, the CVI was 0.99, indicating a high level of agreement. Conclusion: The technology was considered valid by the target audience, health expert judges, and communication judges and can be used as an educational tool, leading the target audience to think more critically and ensuring effectiveness in self-care and health promotion.